An Ecological and Postcolonial Study of Literature - Marzec, R. author. aut Link
VII, 200 p. 1 illus.
Keywords: This book argues that humanity's relationship to the land has undergone a fundamental and calamitous change. Marzec reveals how the historical phenomenon known as the 'enclosure movement' has effected not only the ecosystems and the geopolitics of the Twenty-First century, but on how we relate to the earth and conceive of ourselves as human.